Pengaruh Social Media Marketing on Instagram Melalui Brand Awareness dan Purchase Intention Produk Mangkok Nusantara - Adelia Tiara Nazila; Aria Ganna Henryanto; Irantha Hendrika Kenang (Jurnal Performa : Jurnal Manajemen dan Start-up Bisnis, 2022)
Indonesia is a country that gets technologcal increase that impacts on social media and internet users get more increased annually . Social media also becomes one of the aspect that has very great effect in community environment. The parpose of this research is to research and analyze the effect of social media marketing on Instagram towards brand awareness and purchase intention of Mangkok Nusantara product. The method that is used in this research is quantitative. The population that is used is respondents who know the object of research, that is, Mangkok Nusantara, the sampling technique that is used is purposive sampling technique. The number of samples in this research is 130 respondents. The data collection method uses questionnaire method that uses Likert Scale with Partial Least Square (PLS) analysis method with helping tool of SmartPLS 3.0. The results of this research indicate that social media marketing affects significant on brand awareness, social media marketing affets significant on purchase intention, brand awareness affects significant on purchase intention, brand awareness mediates the relationship between social media marketing and purchase intention of Mangkok Nusantara product.